Electrochemical Sensors for the Estimation of the Inhibitory Effect of Phenylcarbamates to Cholinesterase - Vorčáková Katarína; Štěpánková Šárka; Sedlák Miloš; Vytřas Karel (My University, 2015)
The inhibitory effect of nine phenylcarbamates with various substituents was studied. For this purpose, electrochemical sensors were applied under two different conditions: if an enzyme was present in the solution or if the enzyme was immobilized onto the electrode surface. In both cases, 3-[(ethoxycarbonyl)amino]phenyl (4-chloro-phenyl)carbamate was found as the most effective inhibitor for butyrylcholinesterase. The best inhibitors for acetylcholinesterase were determined as well, depending on the used method. Thus, 3-[(butoxycarbonyl)-amino]phenyl phenylcarbamate with the enzyme present in the solution and 3-[(ethoxycarbonyl)amino]phenyl (3-methylphenyl)carbamate when the enzyme was immobilized onto the electrode surface were evaluated as the most effective inhibitors. Michaelis constants as well as maximum reaction rates were calculated and assessed.
Elektrochemické senzory pro stanovení inhibičního účinku fenylkarbamatů na cholinesterázy
Keywords: biosensors; immobilization of cholinesterases; phenylcarbamates; inhibition; IC50; kinetic parameters; biosenzory; imobilizace cholinesteras; fenylkarbamaty; inhibice; IC50; kinetické parametry